IS THE LAW (POSSIBLY) DEAD OR CAN IT BE KILLED? OR HAS THE STATE FAILED/HAS IT BEEN ABSENT? - Moeliono, Tristam Pascal (Jurnal IUS, 2013)
Law is impossible to die, even if we can strangle it until limp. This questions appeared the possibility of killing the law by tracing the ideas about the law and the state that appears in the passage of time. What emerges is that the order or disorder always presupposes the emergence of law. Although it does not indicate whether the law appear fair or not. The fact is that people need a law although not necessarily requiring the State. Problems faced by Indonesia is now possible to be considered not as a matter of law, but the inability of the StateÂ to present itself as something that is needed by the community.Keywords : Community, Emergence ofÂ Law, Fairness